Daclatasvir plus peginterferon alfa and ribavirin for treatment-naive chronic hepatitis C genotype 1 or 4 infection: a randomised study. Issue 6 (30th July 2014) - Hézode, Christophe; Hirschfield, Gideon M; Ghesquiere, Wayne; Sievert, William; Rodriguez-Torres, Maribel; Shafran, Stephen D; Thuluvath, Paul J; Tatum, Harvey A; Waked, Imam; Esmat, Gamal; Lawitz, Eric J; Rustgi, Vinod K; et al.
Abstract : Objective: To evaluate the safety and efficacy of daclatasvir, an HCV NS5A inhibitor with pangenotypic activity, administered with peginterferon-alfa-2a/ribavirin. Design: In this Phase 2b double-blind, placebo-controlled study, treatment-naive adults with HCV genotype 1 (N=365) or 4 (N=30) infection were randomly assigned (2:2:1) to daclatasvir 20 mg or 60 mg, or placebo once daily plus weekly peginterferon-alfa-2a and twice-daily ribavirin. Daclatasvir recipients achieving protocol-defined response (PDR; HCV-RNA<lower limit of quantitation at Week 4 and undetectable at Week 10) were rerandomised at Week 12 to continue daclatasvir/peginterferon-alfa-2a/ribavirin for 24 weeks total duration or to placebo/peginterferon-alfa-2a/ribavirin for another 12 weeks. Patients without PDR and placebo patients continued peginterferon-alfa/ribavirin through Week 48. Primary efficacy endpoints were undetectable HCV-RNA at Weeks 4 and 12 (extended rapid virologic response, eRVR) and at 24 weeks post-treatment (sustained virologic response, SVR24 ) among genotype 1-infected patients. Results: Overall, eRVR was achieved by 54.4% (80/147) of genotype 1-infected patients receiving daclatasvir 20 mg, 54.1% (79/146) receiving 60 mg versus 13.9% (10/72) receiving placebo. SVR24 was achieved among 87 (59.2%), 87 (59.6%), and 27 (37.5%) patients in these groups, respectively. Higher proportions of genotype 4-infected patients receiving daclatasvir 20 mg (66.7%; 8/12) or 60 mg (100.0%; 12/12) achieved SVR24 versus placebo (50.0%; 3/6). A majority of daclatasvir-treated patients achieved PDR and experienced less virologic failure and higher SVR24 rates with a shortened 24-week treatment duration. Adverse events occurred with similar frequency across all treatment groups. Conclusions: The combination of daclatasvir/peginterferon-alfa/ribavirin was generally well tolerated and achieved higher SVR24 rates compared with placebo/peginterferon-alfa/ribavirin among patients infected with HCV genotype 1 or 4. Trial registration number: NCT01125189.